(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The most distinguished Afro-American writer of 20th century, Zora Neale Hurston, becomes avoice of Black dignity and self-fulfillment. Her writings depict the wretched condition of subjugated Blackwomen who undergo various trials and tribulations in the (white) patriarchal society. Being a Black writer,Race and racism is the dominant feature of her creative venture. In her most acclaimed novel Their EyesWere Watching God, she portrays a poignant expedition of an innocent “nigger” girl who looks forward forthe fulfillment of her innermost desire to love and to be loved as a woman. but within the patriarchalframework she is treated as the other. In fact the Afro-American Literature represents the psyche ofBlack women suffering from trauma within the traumatized societal set up, and marginalized within theframework of gender and race .The author has voiced that how male dominance in society silences thevoice of females. How they make the woman of color , tongue less, eyeless, and earless .Hurstonthrough her writing depicts the plight of Afro American women and the huge oppression andmistreatment they are subjected to especially after marriage. Hurston‟s aim as a writer is not only to freeher community from external prejudices but also from internal menaces. Their Eyes Were Watching Godportrays not only the negative side of “nigger” woman‟s struggle but it also depicts her incessantstruggle to form herself , to voice her desire and to reshape her identity .The protagonist starts herjourney from self-doubt to self-fulfillment from speechless to speech and from impossibilities topossibilities .